Perlindungan Hukum Bagi Investor Berdasarkan Undang-Undang Pasar Modal di Era Digital Dalam Transaksi Reksa Dana - Hermanto, Dennis; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation has had a major impact on the Indonesian stock market, especially in mutual fund transactions through digital media. The easier access and efficiency brought by financial technology has created wider investment opportunities for the public, including those who are just starting to invest. However, this development also brings challenges in terms of legal protection for investors. The existing capital market rules are still based on the old paradigm, so they are not fully able to keep up with the rapid pace of technological development. In addition, there are various technical issues, such as potential data security risks and cyber threats, low public understanding of finance and digital, and differences in access to technology in various regions. The current investor protection strategy still faces obstacles in terms of supervision, law enforcement, and dispute resolution mechanisms that are not yet responsive in the digital age. Therefore, collaboration between flexible regulations, Irusted technology, and programs that improve financial and digital literacy widely and sustainably is needed. By overcoming existing challenges, the digital mutual fund industry in Indonesia can grow inclusively, sustainably, and be able to provide maximum protection for investors in the digital era.